2008
DOI: 10.1097/mrr.0b013e3282f28f38
|View full text |Cite
|
Sign up to set email alerts
|

Towards objective evaluation of balance in the elderly: validity and reliability of a measurement instrument applied to the Tinetti test

Abstract: The aim of the present study was the validation of an instrument for evaluating balance, applied to the Tinetti test. Trunk inclination was measured by inclinometers during the Tinetti test in 163 healthy participants scoring 28/28 in the Tinetti scale (controls: 92 women, 71 men; age 19-85 years), and 111 residents in old people's homes, able to autonomously perform the test, but scoring less than 28/28 (test group: 78 women, 33 men; age 55-96 years). Trunk inclination was quantified by 20 parameters, whose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
1
11
0
4
Order By: Relevance
“…Pérennou et al (29) concluded that Tinetti test is a valid and reliable tool to evaluate the mobility and the risk of falling in older adults, and it is more effective than other tests, such as Berg scale test, but according to our results, both tests can be used to assess balance and gait, supporting evidences from Panella et al (28) who determined that these scales provide a very good reliability about the risk of falling, balance, and gait. The scores obtained with the Berg balance scale seem to be appropriate, as a score of ,45 was shown to be predictive of multiple falls in older adults (4).…”
Section: Discussionsupporting
confidence: 85%
“…Pérennou et al (29) concluded that Tinetti test is a valid and reliable tool to evaluate the mobility and the risk of falling in older adults, and it is more effective than other tests, such as Berg scale test, but according to our results, both tests can be used to assess balance and gait, supporting evidences from Panella et al (28) who determined that these scales provide a very good reliability about the risk of falling, balance, and gait. The scores obtained with the Berg balance scale seem to be appropriate, as a score of ,45 was shown to be predictive of multiple falls in older adults (4).…”
Section: Discussionsupporting
confidence: 85%
“…The Tinetti Performance Oriented Mobility Assessment (POMA) scoring scale is broken down into two parts: a gait portion (maximum score 12) consisting of initiation of gait, step length, step height, step symmetry, step continuity, path, trunk stability, and walking stance; and a balance portion (maximum score 16) consisting of sitting balance, rising, attempting to rise, immediate standing balance, nudging response, eyes closed balance, and turning 360 degrees while sitting down. 30,31 Higher POMA scores correspond to better motor function.…”
Section: Behavioral Assessmentsmentioning
confidence: 99%
“…Typically, balance control is assessed by means of clinical balance scales, that consist in the scoring of a set of simple, everyday-life movements executed in sequence by the patient. The most common scales are: the Tinetti test [4,5], the Berg balance scale [6], and the BEST test [7]. The subject's performance is currently evaluated by the physiatrist or the physiotherapist, who give his/her judgment by means of a numerical score on a predefined scale.…”
Section: Introductionmentioning
confidence: 99%